Weed density and productivity of dry direct seeded rice in relation to weed management practices and seedbed preparation methods - Shah, P.; Sah, S. K.; Basnet, K. B.; Paudel, M. N. (Journal of Agriculture and Forestry University, 2020)
Effective weed management practice is important for successful dry direct seeded rice (DDSR) cultivation. Field experiments were conducted during rainy seasons of 2016 and 2017 to assess the effect of herbicides, or herbicides mixture, and seedbeds preparation methods on weed density and grain yield of DDSR. The experiments were done by using two factors factorial strip plot design with four replications. The treatments consisted of nine weed management practices (weed free; weedy check; spraying Pendimethalin; Bispyribac sodium; Ethoxysulfuron; Pendimethalin followed by Bispyribac sodium; Pendimethalin followed by Ethoxysulfuron; Bispyribac sodium tank mix with Ethoxysulfuron, and Pendimethalin followed by Bispyribac sodium tank mix with Ethoxysulfuron) as horizontal factor whereas two seedbed preparation methods (stale, and normal seedbed) were considered as the vertical factor. The data were collected and analyzed using MSTAT-C statistical software. Total density and dry matter of weeds were significantly (p<0.05) lower in weed free treatment followed by Pendimethalin spray and Bispyribac sodium tank mix with Ethoxysulfuron spray at all the growth stages of rice in both the years. Similarly, rice grain yield was significantly higher (p<0.05) in weed free treatment followed by Pendimethalin spray and Bispyribac sodium tank mix with Ethoxysulfuron spray in both the years. Effect of seedbed preparation methods on weed density and dry matter, yield attributes and yield of rice were non-significant. Therefore, Pendimethalin spray followed by Bispyribac sodium tank mix with Ethoxysulfuron spray seems better option for managing weeds in DDSR.